2023
DOI: 10.1099/jmm.0.001780
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infections: a review of the current diagnostics landscape

Braith Grey,
Mathew Upton,
Lovleen Tina Joshi

Abstract: Urinary tract infections are the most common bacterial infections worldwide. Infections can range from mild, recurrent (rUTI) to complicated (cUTIs), and are predominantly caused by uropathogenic Escherichia coli (UPEC). Antibiotic therapy is important to tackle infection; however, with the continued emergence of antibiotic resistance there is an urgent need to monitor the use of effective antibiotics through better steward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 177 publications
(262 reference statements)
0
2
0
Order By: Relevance
“…Each clinical microbiology laboratory chooses to follow a UTI diagnostic procedure based on the needs and characteristics of the treated population, as reflected in various guidelines [1, 2, 4, 6]. As the published information about the use of these procedures is scarce and out of date, we decided to assess the utility of a 48-hour BA culture in a 7 % CO 2 -enriched atmosphere compared to a 24-hour CRA culture in an aerobic atmosphere to determine the best method for a hospital attending predominantly urological and nephrological patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each clinical microbiology laboratory chooses to follow a UTI diagnostic procedure based on the needs and characteristics of the treated population, as reflected in various guidelines [1, 2, 4, 6]. As the published information about the use of these procedures is scarce and out of date, we decided to assess the utility of a 48-hour BA culture in a 7 % CO 2 -enriched atmosphere compared to a 24-hour CRA culture in an aerobic atmosphere to determine the best method for a hospital attending predominantly urological and nephrological patients.…”
Section: Discussionmentioning
confidence: 99%
“…These recommendations advise performing urine cultures on cysteine–lactose–electrolyte-deficient agar or chromogenic agar (CRA), as well as on blood agar (BA), both types of culture being incubated for 24 hours. Optionally, a prolonged 48-hour incubation period and/or the use of other media cultures are suggested [1–5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary tract infections (UTIs) are one of the most common bacterial infections. 400 million people in the world contracted a UTI in 2019 and more than 230,000 of them died from it (1). UTIs mainly affect women (50-60%) and it has been shown that half of them will have at least one in their life, reducing their quality of life (2).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the gold standard for detection and identification of bacterial cells in urine consists in a microbiological culture, followed by bacterial species identification using MALDI-TOF (matrixassisted laser desorption ionization-time of flight) mass spectrometry analysis (4)(5)(6). Due to the length of this culture, results can only be obtained in 24 to 48h (1,7), delaying appropriate antimicrobial treatment. Moreover, during this time, broad-spectrum antibiotics are often administered to the patient empirically, although this practice has been shown to be responsible for the occurrence of antimicrobial-resistant pathogens in the population (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%